МЕНЕДЖМЕНТ У СИСТЕМІ ПРОФЕСІЙНОЇ ПЕРЕПІДГОТОВКИ ПЕДАГОГІЧНИХ КАДРІВ (Педагогіка вищої та середньої школи, 2004)
This article concerns the abilities of pedagogical management during the process of pedagogical training as one of the ways of professional readiness.